Characterization of the electrical and physical properties of scandium nitride grown using hydride vapor phase epitaxy - Richards, Paul (Kansas State University, 2010)
It is important in semiconductor manufacturing to understand the physical and electrical characteristics of new proposed semiconductors to determine their usefulness. Many tests are used in order to achieve this goal, such as x-ray diffraction, Hall effect measurements, and the scanning electron microscope. With these tests, the usefulness of the semiconductor can be determined, leading to more possibilities for growth in industry. The purpose of the present study was to look at the semiconductor scandium nitride (ScN), grown using the hydride vapor phase epitaxy (HVPE) method on various substrates, and determine the physical and electrical properties of the sample. This study also sought to answer the following questions: 1) Can any trends be found from the results?, and 2) What possible application could scandium nitride be used for in the future? A sample set of scandium nitride samples was selected. Each one of these samples was checked for contaminants from the growth procedure, such as chlorine, under the scanning electron microscope and checked for good conduction of current needed for the Hall effect measurements. The thickness of the scandium nitride layer was computed using the scanning electron microscope. Using the thickness of the scandium nitride, Hall effect measurement values were computed. The plane the samples lie on was checked using x-ray diffraction. The test results shed light on many trends in the scandium nitride. Many of the samples were determined to have an aluminum nitride (AlN) contamination. This contamination led to a much higher resistivity and a much lower mobility no matter what thickness the scandium nitride was. The data from the samples was then used to offer suggestions on how to improve the growth process.
Keywords: Scandium; Nitride; HVPE; Epitaxy; characterization; ScN; Engineering, Chemical (0542); Engineering, Electronics and Electrical (0544)